Odpowiedź:
zad 3
a)
(x² - 1)/(x - 5) * (5 - x)/(x + 1)
założenie:
x - 5 ≠ 0 ∧ x + 1 ≠ 0
x ≠ 5 ∧ x ≠ - 1
D: x ∈ R \ { - 1 , 5 }
(x² - 1)/(x - 5) * (5 - x)/(x + 1) = [(x + 1)(x - 1)]/(x - 5) * - (x - 5)/(x + 1) =
= (x - 1) * - 1 = - (x - 1) = - x + 1
b)
(4x - x²)/(1 - x²) : (- 8 + 2x)/(1 - x)
założenie:
1 - x² ≠ 0 ∧ - 8 + 2x ≠ 0
(1 - x)(1 + x) ≠ 0 ∧ 2(- 4 + x) ≠ 0
x ≠ 1 ∧ x ≠ - 1 ∧ x ≠ 4
D: x ∈ R \ { - 1 , 1 , 4 }
(4x - x²)/(1 - x²) : (- 8 + 2x)/(1 - x) = x(4 - x)/[(1 - x)(1 + x)] * (1 + x)/2(- 4 + x) =
= x(4 - x)/2(- 4 + x) = x(4 - x)/- 2(4 - x) = x/(- 2) = - x/2